PH variability at volcanic CO2 seeps regulates coral calcifying fluid chemistry. (4th February 2022) - Comeau, Steeve; Cornwall, Christopher E.; Shlesinger, Tom; Hoogenboom, Mia; Mana, Ralph; McCulloch, Malcolm T.; Rodolfo‐Metalpa, Riccardo
Abstract: Coral reefs are iconic ecosystems with immense ecological, economic and cultural value, but globally their carbonate‐based skeletal construction is threatened by ocean acidification (OA). Identifying coral species that have specialised mechanisms to maintain high rates of calcification in the face of declining seawater pH is of paramount importance in predicting future species composition, and growth of coral reefs. Here, we studied multiple coral species from two distinct volcanic CO2 seeps in Papua New Guinea to assess their capacity to control their calcifying fluid (CF) chemistry. Several coral species living under conditions of low mean seawater pH, but with either low or high variability in seawater pH, were examined and compared with those living in 'normal' (non‐seep) ambient seawater pH. We show that when mean seawater pH is low but highly variable, corals have a greater ability to maintain constant pHcf in their CF, but this characteristic was not linked with changes in abundance. Within less variable low pH seawater, corals with limited reductions in pHcf at the seep sites compared with controls tended to be more abundant at the seep site than at the control site. However, this finding was strongly influenced by a single species ( Montipora foliosa ), which was able to maintain complete pHcf homeostasis. Overall, although our findings indicate that there might be an association between ecological success and greater pHcf homeostasis, further research with additional species and at more sites with differing seawater pH regimes is required to solidify inferences regarding coral ecological success under future OA. Abstract : We studied multiple coral species from two distinct volcanic CO2 seeps in Papua New Guinea (Graphical abstract figure) to assess their capacity to control their calcifying fluid chemistry, a key parameter involved in producing their calcium carbonate skeleton. We show that pH variability can affect the control of the corals' calcifying fluid chemistry. Our study also indicates that there might be an association between ecological success and greater calcifying fluid pH homeostasis (i.e., the capacity to maintain pH constant in the calcifying fluid under different seawater pH).